The possibility of healing alveolar bone defects with simvastatin thermosensitive gel: in vitro/in vivo evaluation - Ruan H; Yu Y; Guo X; Jiang Q; Luo Y (Dove Medical Press, 2018)
Hong Ruan, Youcheng Yu, Xuehua Guo, Qian Jiang, Ying Luo Department of Stomatology, Zhongshan Hospital, Fudan University, Shanghai, China Background: In this study, simvastatin (SVT) in situ gels were successfully produced by our group. Methods: The preparations were characterized in the following aspects: in vitro gelation, drug release, stability and pharmacodynamics. Results: In this study, drug content of prepared gels was found to be in the range between 89 and 92%. The pH value was in the range between 6.5 and 7.0. The gelation temperature of the prepared thermogelling solutions was 37°C. In vitro release showed that the release of SVT from in situ gels was slow with burst effects at an early stage. Researches indicated that intraorally slow release SVT in situ gels could effectively promote bone regeneration repair of alveolar bone defect. Conclusion: This drug delivery system could prove to be a novel form able to prolong the residence time and to control the release of drug when administered into the oral cavity. Keywords: SVT, in situ gel, thermogelling, gelation, in vitro release, alveolar bone defect